Investigation of Surface Thermodynamic Properties and Structural Isomer Separation Capability of Sodium Alginate/Hypericum perforatum Composites - Guven, Meltem; Erdogan Cakar, Ayse; Isik, Birol; Cankurtaran, Ozlem (WILEY-V C H VERLAG GMBH, 2026)
In the present investigation, biocomposites were created by inserting the biomass of Hypericum perforatum (HP), which is regarded as a material that generates zero waste, into a biopolymer composed of sodium alginate (SA) at weight ratios of 10%, 20%, and 30%. Using Fourier transform infrared-attenuated total reflectance (FTIR-ATR) spectroscopy, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD) studies, the biocomposites that were produced were analyzed and described. Inverse gas chromatography (IGC) was used to explore the surface properties of these materials throughout a temperature range of 303.2-328.2 K. The Dorris-Gray, Donnet-Park, Schultz, and Hamieh methods were utilized in this investigation. The determination of the specific adsorption enthalpy, the specific adsorption free energy, and the acid-base constants for both HP and the SA/HP composites was made possible using experiments that were carried out at an infinite dilution. Additionally, the selectivity coefficients (alpha) of structural isomers were determined at infinite dilution for a variety of acetate and alcohol isomers within the same temperature range. This was accomplished by employing the IGC technique.
Keywords: hypericum perforatum; isomer separation; sodium alginate; LIQUID-CRYSTAL; GAS-CHROMATOGRAPHY; FIBERS; FILMS; Polymer Science